River recharge versus O2 supply from the unsaturated zone in shallow riparian groundwater: A case study from the Selke River (Germany) - Mader, Michael; Roberts, André Michael; Porst, David; Schmidt, Christian; Trauth, Nico; van Geldern, Robert; Barth, Johannes (Science of the Total Environment, 2018)
Besides gas-water-exchange in surface waters, respiratory consumption of dissolved oxygen (DO) in adjacent riparian groundwater may trigger the addition of so far hardly explored sources from the unsaturated zone. These processes also systematically influence stable isotope ratios of DO and were investigated together with Cl− as a conservative tracer for water mixing in a near-river riparian groundwater system. The study focused on a losing stream section of the Selke River at the foot of the Harz Mountains (Germany). The study area exposed steep DO gradients between the stream water and riparian groundwater between April 2016 and May 2017. Our results indicated dominant influences of microbial community respiration with observed DO concentration gradients. These observations can be explained by DO from the river that is subject to fractionation by microbial respiration with a typical fractionation factor (αr) of 0.982. However, with such respiration dominance, we expected a simultaneous enrichment of δ18ODO towards values that are more positive than the well-known atmospheric O2 signal of +23.9‰ versus the Vienna Standard Mean Ocean Water standard (VSMOW). Surprisingly, our measurements revealed much lower δ18ODO values between +22‰ and +18‰ in the near-river groundwater. Mass balance calculations revealed that the DO pool in the shallow and unconfined aquifer receives contributions of up to about 80% by diffusion of oxygen from the vadose zone with a distinctly lower isotope value than the one of the atmosphere. This finding about additional oxygen sources from the unsaturated zone has numerous ramifications for oxygen related processes in near-river environments including the oxidation of pollutants, nutrients and ecosystem health.
Keywords: Riparian zone; Dissolved oxygen; Stable isotopes; Diffusion; Vadose zone